Narrative Intelligence and Pedagogical Success in English - Pishghadam, Reza; Golparvar, Seyed Ehsan; Khajavy, Gholam Hassan; Iranrad, Elaheh (BELT - Brazilian English Language Teaching Journal, 2012)
<span style="font-size: 12.0pt; line-height: 200%; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; color: black; mso-themecolor: text1;">The present study intends to investigate the relationship between English as a Foreign Language (EFL) teachers’ narrative intelligence and their pedagogical success. Eighty EFL teachers along with 673 EFL learners participated in this study. Narrative Intelligence Scale (NIS) and the Characteristics of the Successful Teachers Questionnaire (CSTQ) were utilized to gather data in this study. The results revealed that there exists a significant association between EFL teachers’ pedagogical success and their narrative intelligence. Moreover, Genre-ation, among the subscales of narrative intelligence, was found to be the best predictor of teacher success. Finally, the results were discussed and pedagogical implications were provided in the context of language learning and teaching.